Tata Kelola Teknologi Informasi Menggunakan COBIT 2019 Pada Val - Berliana Angel M. Pangaribuan; Sandhy Fernandez (Pixel :Jurnal Ilmiah Komputer Grafis, 2023)
Technology information (IT) has been widely adopted across sectors like healthcare, education, governance, and business, playing a crucial role in facilitating relationships between businesses and stakeholders. However, Val, a business that has incorporated technology, lacks an analysis of information technology governance. Consequently, Val faces challenges in effectively aligning their technology usage with their business objectives. This research aims to assess Val's information technology practices, recommend improvement measures, and achieve desired capability targets. Utilizing the COBIT 2019 framework and the design factor toolkit, two priority Governance and Management Objectives (GMOs) have been identified: APO04 (Managed Innovation) and DSS05 (Managed Security Services). APO04 currently operates at capability level 2, falling 2 levels short of the desired capability level, while DSS05 operates at capability level 1, with a gap of 3 levels.